Effects of heating rate and AAEM on the production of NH3 and HCN during pyrolysis of shengli brown coal - Zhang, Shu; Bai, Y.; Xu, D.; Zheng, P.; Bai, L.; Wang, Y. (2013)
This study is to examine the effects of heating rate and AAEM (alkali and alkaline earth metallic species) on the generation of NH 3 and HCN during the pyrolysis of Shengli brown coals at two different temperatures of 773 and 1073 K. All the experiments were conducted in a fixed-bed/fluidised-bed quartz reactor. The results show that high heating rate and high temperature have substantially promoted the formation of both NH 3 and HCN. By comparing the results from raw coal and acid-washed coal, it was found that reduction in AAEM (mainly Na and Ca in this case) could lead to less production of NH3, but more formation of HCN. Copyright © (2013) by the International Pittsburgh Coal Conference.